2016
DOI: 10.1037/pspp0000060
|View full text |Cite
|
Sign up to set email alerts
|

The development of global and domain-specific self-esteem from age 13 to 31.

Abstract: This study examines the development of global self-esteem and self-esteem in 6 specific domains across adolescence and young adulthood. Using a cohort-sequential design, we analyzed longitudinal data on 3,116 Norwegian men and women from 13 to 31 years of age by means of growth curve modeling. Questionnaire data provided information on global self-esteem and self-esteem in social, academic, athletic, and appearance domains. Data on important life outcomes was provided by register linkages. Results showed incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
5
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(199 citation statements)
references
References 79 publications
(212 reference statements)
12
170
5
12
Order By: Relevance
“…Further, we will explore which domains of self-esteem (i.e., scholastic competence, social acceptance, athletic competence, physical appearance, and romantic appeal) contribute with significant unique variance to QoL. In these analyses, we adjust for gender and age because QoL has shown to be gender and age dependent in earlier studies [29], and pronounced gender and age differences have been detected in psychopathology [30,31] and self-esteem [20,32]. Figure 1 depicts the associations to be investigated in our structural equation model.…”
Section: Aims Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Further, we will explore which domains of self-esteem (i.e., scholastic competence, social acceptance, athletic competence, physical appearance, and romantic appeal) contribute with significant unique variance to QoL. In these analyses, we adjust for gender and age because QoL has shown to be gender and age dependent in earlier studies [29], and pronounced gender and age differences have been detected in psychopathology [30,31] and self-esteem [20,32]. Figure 1 depicts the associations to be investigated in our structural equation model.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…(5) Romantic Appeal referring to perceptions of romantic appeal, for example, ''I feel that people of my age will be romantically attracted to me.'' A longitudinal epidemiological study of Norwegian adolescents and young adults [35] reported satisfactory internal consistency for these five domains (Scholastic Competence a = .69-.71; Social Acceptance a = .77-.83; Athletic Competence a = .79-.82; Physical Appearance a = .86-.90; and Romantic Appeal a = .75).…”
Section: Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation
“…La dimensión académica, definida por las autoras como la autopercepción de la capacidad para enfrentar con éxito las situaciones de la vida escolar, se encuentra dentro de los indicadores de Desarrollo Personal y Social que considera la evaluación nacional, complementaria al logro de los Estándares de Aprendizaje en Chile (Agencia de Calidad de la Educación, 2016). La autoestima física, definida como el hecho de sentirse atractivo físicamente, durante la adolescencia se describe como factor determinante de la autoestima global (Von Soest, Wichstrøm, y Kvalem, 2015). La correlación entre la autoestima global y la dimensión social de ésta, definida como el sentimiento de sentirse aceptado o rechazado por los iguales y el sentimiento de pertenencia, aumenta gradualmente con la edad, lo que se relacionaría con la progresiva autonomía de los jóvenes e independencia de sus padres (Haeussler y Milicic, 2014;Von Soest et al, 2015).…”
Section: Autoestimaunclassified
“…La autoestima física, definida como el hecho de sentirse atractivo físicamente, durante la adolescencia se describe como factor determinante de la autoestima global (Von Soest, Wichstrøm, y Kvalem, 2015). La correlación entre la autoestima global y la dimensión social de ésta, definida como el sentimiento de sentirse aceptado o rechazado por los iguales y el sentimiento de pertenencia, aumenta gradualmente con la edad, lo que se relacionaría con la progresiva autonomía de los jóvenes e independencia de sus padres (Haeussler y Milicic, 2014;Von Soest et al, 2015).…”
Section: Autoestimaunclassified